Preparation method and application of iron phthalocyanine and sulfur-doped porous carbon composite catalyst

By doping porous carbon composite catalyst with iron phthalocyanine and sulfur, the problem of low efficiency of oxygen electrocatalysts in zinc-empty batteries is solved, and high-performance oxygen electrocatalytics and stability improvements are achieved. It is suitable for zinc-empty batteries, with low cost and Environmentally friendly characteristics.

CN119275302AActive Publication Date: 2025-01-07HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411407618.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

Due to the lack of excellent dual-function oxygen electrocatalysts during charging and discharging of zinc-air batteries, the kinetics and low energy efficiency are slow. The existing precious metal catalysts have problems such as low reserves, high prices and insufficient bifunctionality.

Method used

The composite catalyst of iron phthalocyanine and sulfur doped porous carbon is prepared by ball milling process, and the composite catalyst is formed with iron phthalocyanine in DMF solution to break the planar structure symmetry of iron phthalocyanine and enhance the Its oxygen catalytic activity and stability.

Benefits of technology

It realizes high-performance oxygen electrocatalysis, improves the charging and discharging performance and cycle stability of zinc-air batteries, and has the advantages of low cost, mass production and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275302A_ABST
    Figure CN119275302A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an iron phthalocyanine and sulfur-doped porous carbon composite catalyst, which comprises the following steps: S1, preparation of a sulfur-doped porous carbon material: firstly, uniformly mixing coal pitch, KOH and nano ZnO through a ball milling process, and calcining and carbonizing the mixture in a nitrogen atmosphere; soaking the carbonized sample in diluted hydrochloric acid, thoroughly cleaning with distilled water after removing nano ZnO, and drying to obtain a sulfur-doped porous carbon material; s2, compounding iron phthalocyanine and sulfur-doped porous carbon: adding the sulfur-doped porous carbon material and iron phthalocyanine into a DMF (Dimethyl Formamide) solution, magnetically stirring, cleaning a sample, and drying to obtain the iron phthalocyanine and sulfur-doped porous carbon composite catalyst. The prepared composite catalyst shows excellent ORR catalytic performance and stability, and when the composite catalyst is applied to the zinc-air battery, the battery shows good charge-discharge performance and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage materials, and more specifically, to a preparation method and application of an iron phthalocyanine and sulfur-doped porous carbon composite catalyst. Background Art

[0002] Rechargeable metal zinc-air batteries (referred to as "zinc-air batteries"), as a new type of green and environmentally friendly energy storage device, have developed rapidly in recent years. Zinc-air batteries are electrochemical cells with air electrodes as positive electrodes and metal zinc electrodes as negative electrodes. During discharge, oxygen reduction reaction (ORR) occurs at the air electrode; during charging, oxygen evolution reaction (OER) occurs at the air electrode. Since the active substance (oxygen) does not occupy the internal space of the battery, zinc-air batteries have a higher theoretical energy density (1218Wh / kg and 6136Wh / L) than traditional closed batteries, which can meet the needs of large-scale applications. Therefore, zinc-air batteries are expected to shine in the fields of large-scale power grid energy storage, electric vehicles, wearable electronic products, etc.

[0003] However, since the air positive electrode of the zinc-air battery needs to undergo a four-electron ORR / OER reaction during the charge and discharge process, the battery kinetics are slow. And due to the lack of excellent bifunctional ORR / OER catalysts, the energy efficiency of zinc-air batteries is low. Therefore, it is necessary to construct a high-performance ORR / OER bifunctional catalyst to participate in the above process. At present, precious metal catalysts (such as platinum, iridium, ruthenium, etc.) show relatively excellent oxygen electrocatalytic performance, but the problems of low reserves, high prices, insufficient bifunctionality, and easy poisoning of precious metal catalysts seriously restrict their application in this regard. Non-precious metal catalysts have attracted widespread attention from researchers due to their abundant reserves, low prices, and adjustable advantages. Among them, iron phthalocyanine molecular catalysts are considered to be a good oxygen catalyst. However, due to the planar structure of iron phthalocyanine itself, the catalytic activity of iron phthalocyanine is limited, and its reaction stability is reduced. Therefore, the present invention designs an iron phthalocyanine composite catalyst material to improve its oxygen catalytic activity and stability, and is used as a class of efficient oxygen catalysts in zinc-air batteries. Summary of the invention

[0004] The invention provides a method for preparing an iron phthalocyanine and sulfur-doped porous carbon composite catalyst. The prepared composite catalyst exhibits excellent ORR catalytic performance and stability.

[0005] A method for preparing a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon comprises the following steps:

[0006] S1. Preparation of sulfur-doped porous carbon material: firstly, coal tar pitch, KOH and nano ZnO were mixed evenly by ball milling process, and the mixture was calcined and carbonized in nitrogen atmosphere; then, the carbonized sample was immersed in dilute hydrochloric acid, and after removing the nano ZnO, it was thoroughly washed with distilled water and dried to obtain sulfur-doped porous carbon material;

[0007] S2. Composite of iron phthalocyanine and sulfur-doped porous carbon: Add sulfur-doped porous carbon material and iron phthalocyanine into DMF solution, and after magnetic stirring, clean and dry the sample to obtain a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon.

[0008] Preferably, in step S1, the mixing ratio of coal tar pitch, KOH and nano ZnO is 1:3-5:5-8.

[0009] Preferably, in step S1, the calcination temperature is 600-900° C., and the calcination time is 1-2 hours.

[0010] Preferably, in step S1, the concentration of dilute hydrochloric acid is 3 to 7 mol / L, and the soaking time is 6 to 12 hours.

[0011] Preferably, in step S1, the coal tar pitch is a high-temperature petroleum asphalt in the form of powder, with a particle size of 3 to 5 μm, a softening point of 275 to 285° C., and a residual carbon rate of ≥75%.

[0012] Preferably, in step S2, the ratio of sulfur-doped porous carbon material to iron phthalocyanine is 3 to 10:1.

[0013] Preferably, in step S2, the stirring temperature is 40-80° C., and the stirring time is 7-12 h.

[0014] Preferably, in step S2, the purity of the DMF solution is 99.8%.

[0015] In the technical solution of the present invention, the sulfur-doped porous carbon material is obtained by carbonizing coal tar pitch, and KOH and nano ZnO mainly play the role of activation and pore formation during the carbonization process. Since coal tar pitch itself contains sulfur, sulfur-doped porous carbon is obtained after carbonization. In addition, the composite of iron phthalocyanine and sulfur-doped porous carbon makes iron phthalocyanine vertically grafted on the sulfur-doped porous carbon to form a stable three-dimensional structure, eliminating the plane symmetry of iron phthalocyanine FeN 4 Site pair O 2 The Fe site interacts with the S site of sulfur-doped porous carbon to form Fe-S coordination, making S-FeN 4 The electron localization on the axial direction enhances the 2 Adsorption and activation of the composite catalyst. For details on the structure of the composite catalyst, see Figure 1The composite structure breaks the symmetry of the geometric structure and electronic structure of iron phthalocyanine, optimizes the adsorption of reaction intermediates, improves the intrinsic catalytic activity of the catalytic site, and also improves the stability of the catalyst itself. Therefore, the composite catalyst exhibits good catalytic activity and stability.

[0016] The invention also provides an application of the iron phthalocyanine and sulfur-doped porous carbon composite catalyst in a zinc-air battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The structural defects of iron phthalocyanine have always been the main factor affecting its catalytic performance. When the present invention combines iron phthalocyanine with sulfur-doped porous carbon materials, the S site is fixed to the iron phthalocyanine by forming Fe-S coordination, thereby strengthening the interaction between iron phthalocyanine and sulfur-doped porous carbon, improving the planar structural defects and electronic defects of iron phthalocyanine itself, and enhancing the intrinsic catalytic activity and stability of the composite catalyst, and it can be applied to high-performance zinc-air batteries.

[0019] (2) The iron phthalocyanine and sulfur-doped porous carbon composite catalyst prepared by the present invention has a high specific surface area, good electrical conductivity, and exhibits excellent oxygen electrocatalytic performance; when it is applied to a zinc-air battery, the battery exhibits good charge and discharge performance and cycle stability.

[0020] (3) The present invention uses a simple solution method to composite iron phthalocyanine with sulfur-doped porous carbon materials to achieve the purpose of compensating for the structural defects of iron phthalocyanine, and has the advantages of simple operation, low energy consumption, and good repeatability.

[0021] (4) The present invention obtains sulfur-doped porous carbon materials by one-step carbonization of coal tar, which is simpler and more efficient than the traditional preparation of sulfur-doped carbon materials. At the same time, since no additional sulfur source needs to be added and the synthetic raw materials are cheap, the obtained carbon materials have the advantages of low cost and mass production. In addition, by using coal tar waste, the purpose of waste recycling can be achieved, environmental pollution can be reduced, and new application methods for coal tar can be developed. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) is a schematic diagram of the structure of iron phthalocyanine catalyst (FePc). Figure 1 (b) is a schematic diagram of the structure of the iron phthalocyanine and sulfur-doped porous carbon composite catalyst (FePc@PDC) of the present invention.

[0023] Figure 2 (a) and (b), Figure 2 (c) and (d) are scanning electron microscope (SEM) images of the sulfur-doped porous carbon material (PDC) and FePc@PDC of Example 1 at different magnifications, respectively.

[0024] Figure 3 X-ray diffraction (XRD) spectra of FePc@PDC of Example 1, PDC of Comparative Example 1, and FePc of Comparative Example 2.

[0025] Figure 4 BET specific surface area curves of FePc@PDC of Example 1, PDC of Comparative Example 1, and FePc of Comparative Example 2.

[0026] Figure 5 (a) is the LSV curve of ORR measured at different rotation speeds for FePc@PDC of Example 1; Figure 5 (b) is the LSV curve of FePc@PDC of Example 1, PDC of Comparative Example 1, and FePc of Comparative Example 2 at 1600 rpm.

[0027] Figure 6 (a) and (b) are the open circuit voltage, discharge curve and corresponding power density curve of the zinc-air battery assembled with FePc@PDC in Example 1, respectively.

[0028] Figure 7 This is the cycle life curve of the zinc-air battery assembled with FePc@PDC in Example 1. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0030] Example 1

[0031] A method for preparing a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon comprises the following steps:

[0032] S1. Preparation of sulfur-doped porous carbon material: First, 0.5g coal tar (particle size 5μm, softening point 278℃, residual carbon rate 75%), 2g KOH, and 3g nano ZnO were mixed evenly by ball milling process, and the mixing ratio was 1:4:6; the mixture was calcined and carbonized in a nitrogen atmosphere, the calcination temperature was 800℃, and the calcination time was 2h. Then the carbonized sample was soaked in 3mol / L dilute hydrochloric acid for 12h, and after removing the nano ZnO, it was thoroughly washed with distilled water and dried at 80℃ to obtain the sulfur-doped porous carbon material;

[0033] S2. Composite of iron phthalocyanine and sulfur-doped porous carbon: add 200 mg of sulfur-doped porous carbon material and 40 mg of iron phthalocyanine to 200 mL of DMF solution with a purity of 99.8%, and the addition ratio of the two is 5:1; after magnetic stirring at a stirring temperature of 80°C and a stirring time of 12 h, the sample is cleaned and dried at 80°C to obtain a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon.

[0034] Example 2

[0035] A method for preparing a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon comprises the following steps:

[0036] S1. Preparation of sulfur-doped porous carbon material: First, 0.5g coal tar (particle size 5μm, softening point 278℃, residual carbon rate 75%), 2.5g KOH, and 3.5g nano ZnO were mixed evenly by ball milling process, and the mixing ratio was 1:5:7; the mixture was calcined and carbonized in a nitrogen atmosphere, the calcination temperature was 900℃, and the calcination time was 1h. Then the carbonized sample was soaked in 5mol / L dilute hydrochloric acid for 8h, and after removing the nano ZnO, it was thoroughly washed with distilled water and dried at 80℃ to obtain the sulfur-doped porous carbon material;

[0037] S2. Composite of iron phthalocyanine and sulfur-doped porous carbon: add 200 mg of sulfur-doped porous carbon material and 50 mg of iron phthalocyanine to 200 mL of DMF solution with a purity of 99.8%, and the addition ratio of the two is 4:1; after magnetic stirring at a stirring temperature of 60°C and a stirring time of 8 hours, clean the sample and dry it at 80°C to obtain a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon.

[0038] Example 3

[0039] A method for preparing a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon comprises the following steps:

[0040] S1. Preparation of sulfur-doped porous carbon material: First, 0.5g coal tar pitch (particle size 5μm, softening point 278℃, residual carbon rate 75%), 1.5g KOH, and 2.5g nano ZnO were mixed evenly by ball milling process, and the mixing ratio was 1:3:5; the mixture was calcined and carbonized in a nitrogen atmosphere, the calcination temperature was 600℃, and the calcination time was 2h. Then the carbonized sample was soaked in 6mol / L dilute hydrochloric acid for 6h, and after removing the nano ZnO, it was thoroughly washed with distilled water and dried at 80℃ to obtain the sulfur-doped porous carbon material;

[0041] S2. Composite of iron phthalocyanine and sulfur-doped porous carbon: add 200 mg of sulfur-doped porous carbon material and 40 mg of iron phthalocyanine to 200 mL of DMF solution with a purity of 99.8%, and the addition ratio of the two is 5:1; after magnetic stirring at a stirring temperature of 80°C and a stirring time of 12 h, the sample is cleaned and dried at 80°C to obtain a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon.

[0042] Example 4

[0043] A method for preparing a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon comprises the following steps:

[0044] S1. Preparation of sulfur-doped porous carbon material: First, 0.5g coal tar (particle size 5μm, softening point 278℃, residual carbon rate 75%), 2g KOH, and 3g nano ZnO were mixed evenly by ball milling process, and the mixing ratio was 1:4:6; the mixture was calcined and carbonized in a nitrogen atmosphere, the calcination temperature was 800℃, and the calcination time was 2h. Then the carbonized sample was soaked in 3mol / L dilute hydrochloric acid for 12h, and after removing the nano ZnO, it was thoroughly washed with distilled water and dried at 80℃ to obtain the sulfur-doped porous carbon material;

[0045] S2. Composite of iron phthalocyanine and sulfur-doped porous carbon: add 200 mg of sulfur-doped porous carbon material and 20 mg of iron phthalocyanine to 200 mL of DMF solution with a purity of 99.8%, and the addition ratio of the two is 10:1; after magnetic stirring at a stirring temperature of 40°C and a stirring time of 11 h, the sample is cleaned and dried at 80°C to obtain a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon.

[0046] Comparative Example 1

[0047] The sulfur-doped porous carbon material prepared in step S1 of Example 1.

[0048] Comparative Example 2

[0049] A method for preparing an iron phthalocyanine catalyst: commercial iron phthalocyanine is added into 200 mL of a DMF solution with a purity of 99.8%, and the solution is magnetically stirred at a stirring temperature of 80° C. for 12 h, and then the sample is cleaned and dried at 80° C. to obtain the iron phthalocyanine catalyst.

[0050] Comparative Example 3

[0051] A preparation method for an iron phthalocyanine and carbon composite material: 200 mg of acetylene black and 40 mg of iron phthalocyanine are added into 200 mL of a DMF solution with a purity of 99.8%, and the addition ratio of the two is 5:1; after magnetic stirring at a stirring temperature of 80° C. and a stirring time of 12 h, the sample is cleaned and dried at 80° C. to obtain the iron phthalocyanine and carbon composite material.

[0052] Comparative Example 4

[0053] A method for preparing a composite material of iron phthalocyanine and sulfur-doped carbon comprises the following steps:

[0054] S1. Preparation of sulfur-doped carbon material: First, 0.5 g of coal tar (particle size 5 μm, softening point 278°C, residual carbon rate 75%) was ground by ball milling, and the obtained coal tar powder was calcined and carbonized in a nitrogen atmosphere at a calcination temperature of 800°C for 2 h. Then the carbonized sample was soaked in 3 mol / L dilute hydrochloric acid for 12 h, and finally thoroughly washed with distilled water and dried at 80°C to obtain a sulfur-doped carbon material.

[0055] S2. Composite of phthalocyanine iron and sulfur-doped carbon: add 200 mg of sulfur-doped carbon and 40 mg of phthalocyanine iron to 200 mL of 99.8% pure DMF solution, and the addition ratio is 5:1; after magnetic stirring at 80°C and 12 h, the sample is cleaned and dried at 80°C to obtain a phthalocyanine iron and sulfur-doped carbon composite material.

[0056] Comparative Example 5

[0057] A method for preparing a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon comprises the following steps:

[0058] S1. Preparation of sulfur-doped porous carbon material: First, 0.5g coal tar pitch (particle size 5μm, softening point 278℃, residual carbon rate 75%), 1g KOH, and 2g nano ZnO were mixed evenly by ball milling process, and the mixing ratio was 1:2:4; the mixture was calcined and carbonized in a nitrogen atmosphere, the calcination temperature was 500℃, and the calcination time was 3h. Then the carbonized sample was soaked in 3mol / L dilute hydrochloric acid for 12h, and after removing the nano ZnO, it was thoroughly washed with distilled water and dried at 80℃ to obtain the sulfur-doped porous carbon material;

[0059] S2. Composite of iron phthalocyanine and sulfur-doped porous carbon: add 200 mg of sulfur-doped porous carbon material and 40 mg of iron phthalocyanine to 200 mL of DMF solution with a purity of 99.8%, and the addition ratio of the two is 5:1; after magnetic stirring at a stirring temperature of 80°C and a stirring time of 12 h, the sample is cleaned and dried at 80°C to obtain a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon.

[0060] Comparative Example 6

[0061] A method for preparing a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon comprises the following steps:

[0062] S1. Preparation of sulfur-doped porous carbon material: First, 0.5g coal tar (particle size 5μm, softening point 278℃, residual carbon rate 75%), 2g KOH, and 3g nano ZnO were mixed evenly by ball milling process, and the mixing ratio was 1:4:6; the mixture was calcined and carbonized in a nitrogen atmosphere, the calcination temperature was 800℃, and the calcination time was 2h. Then the carbonized sample was soaked in 3mol / L dilute hydrochloric acid for 12h, and after removing the nano ZnO, it was thoroughly washed with distilled water and dried at 80℃ to obtain the sulfur-doped porous carbon material;

[0063] S2. Composite of iron phthalocyanine and sulfur-doped porous carbon: add 200 mg of sulfur-doped porous carbon material and 100 mg of iron phthalocyanine to 200 mL of DMF solution with a purity of 99.8%, and the addition ratio of the two is 2:1; after magnetic stirring at a stirring temperature of 90°C and a stirring time of 6 hours, the sample is cleaned and dried at 80°C to obtain a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon.

[0064] The test results of the materials obtained in Examples 1 to 4 and Comparative Examples 1 to 6 are shown in the following table:

[0065]

[0066] In addition, the performance test results of FePc@PDC of Example 1, PDC of Comparative Example 1, and FePc of Comparative Example 2 are as follows: Figures 2 to 7 shown.

[0067] Figure 2 In the figure, it can be observed from (a) and (b) that the PDC synthesized in Example 1 is a carbon material with a rich porous structure; from (c) and (d) it can be observed that the iron phthalocyanine molecules in the prepared FePc@PDC are uniformly dispersed on the sulfur-doped porous carbon material to form a uniform composite material, and the pores of FePc@PDC are reduced compared to PDC. This is because the porosity of FePc is smaller than that of PDC, so the porosity of the composite material is smaller than that of PDC, and the pores will also be reduced.

[0068] Figure 3 In the figure, it can be seen that the PDC of Comparative Example 1 shows the diffraction peak of carbon (JCPDS#75-2078) at the (111) crystal plane, and the FePc of Comparative Example 2 shows the diffraction peak corresponding to iron phthalocyanine. The diffraction peaks of carbon and iron phthalocyanine appear simultaneously in the FePc@PDC of Example 1, indicating the successful synthesis of the composite catalyst.

[0069] Figure 4 It can be seen that the PDC of Comparative Example 1 has the largest specific surface area, which is 1375.69 m 2 / g; The specific surface area of ​​FePc@PDC in Example 1 is slightly smaller than that of PDC, which is 1017.57m2 / g, and the specific surface areas of the two are consistent with the SEM results. The specific surface area of ​​FePc in comparative example 2 is 15.91m 2 / g, which is much smaller than that of PDC and FePc@PDC. This indicates that after the composite of iron phthalocyanine and sulfur-doped porous carbon material, the presence of porous structure makes the specific surface area significantly increased, which is beneficial to expose more active sites to participate in the catalytic reaction and enhance the catalytic performance of the composite catalyst.

[0070] Figure 5 In (a), it can be seen that the limiting current density of FePc@PDC in Example 1 increases steadily with the increase of the test rotation speed; when the rotation speed reaches the maximum, its limiting current reaches the maximum. Figure 5 In (b), it can be seen that under the condition of 1600 rpm, compared with the PDC of Comparative Example 1, the FePc of Comparative Example 2 and the precious metal Pt / C catalyst, the half-wave potential of the FePc@PDC composite catalyst of Example 1 is significantly higher than that of PDC and FePc, and is close to that of the Pt / C catalyst, indicating that the FePc@PDC composite catalyst has good ORR catalytic performance.

[0071] Figure 6 In (a), it can be seen that the zinc-air battery assembled with FePc@PDC in Example 1 has a high open circuit voltage of 1.56 V; Figure 6 (b) It can also be seen that during the discharge process of the zinc-air battery, its maximum current can reach 165 mA cm -2 , and the peak power density reached 74mW cm -2 .

[0072] Figure 7 It can be seen that the zinc-air battery assembled with FePc@PDC in Example 1 has a higher discharge voltage and a lower charge voltage, indicating that the battery has a good charge and discharge efficiency. In addition, after the battery has been stably cycled for 17 hours, the charge and discharge performance remains unchanged, indicating that the battery has good charge and discharge performance and a stable cycle life.

[0073] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon, characterized in that: The following steps are involved: S1. Preparation of sulfur-doped porous carbon material: firstly, coal tar pitch, KOH and nano ZnO were mixed evenly by ball milling process, and the mixture was calcined and carbonized in nitrogen atmosphere; then, the carbonized sample was immersed in dilute hydrochloric acid, and after removing the nano ZnO, it was thoroughly washed with distilled water and dried to obtain sulfur-doped porous carbon material; S2. Composite of iron phthalocyanine and sulfur-doped porous carbon: Add sulfur-doped porous carbon material and iron phthalocyanine into DMF solution, and after magnetic stirring, clean and dry the sample to obtain a composite catalyst of iron phthalocyanine and sulfur-doped porous carbon.

2. The preparation method according to claim 1, characterized in that In the step S1, the mixing ratio of coal tar pitch, KOH and nano ZnO is 1:3-5:5-8.

3. The preparation method according to claim 2, characterized in that: In the step S1, the calcination temperature is 600-900° C., and the calcination time is 1-2 hours.

4. The preparation method according to claim 3, characterized in that: In step S1, the concentration of the dilute hydrochloric acid is 3 to 7 mol / L, and the soaking time is 6 to 12 hours.

5. The preparation method according to claim 1, characterized in that: In the step S1, the coal tar pitch is a high-temperature petroleum asphalt in the form of powder, with a particle size of 3 to 5 μm, a softening point of 275 to 285° C., and a residual carbon rate of ≥75%.

6. The preparation method according to claim 1, characterized in that: In the step S2, the ratio of sulfur-doped porous carbon material to iron phthalocyanine is 3 to 10:

1.

7. The preparation method according to claim 6, characterized in that: In step S2, the stirring temperature is 40 to 80° C., and the stirring time is 7 to 12 hours.

8. The preparation method according to claim 7, characterized in that: In step S2, the purity of the DMF solution is 99.8%.

9. An iron phthalocyanine and sulfur-doped porous carbon composite catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the composite catalyst according to claim 9 in zinc-air batteries.

Citation Information

Patent Citations

  • Preparation method of carbon based catalyst with high graphitization degree and used for fuel cell cathode

    CN104289242A

  • Iron phthalocyanine / copper phthalocyanine / pitch coke activated carbon Li / SOCl2 battery positive electrode catalytic material and preparation method thereof

    CN112871217A